2014
DOI: 10.5489/cuaj.2258
|View full text |Cite
|
Sign up to set email alerts
|

The clinical research office of the endourological society percutaneous nephrolithotomy global study: Outcomes in the morbidly obese patient – a case control analysis

Abstract: Background: Efficacy and safety of percutaneous nephrolithotomy (PCNL) have been demonstrated in obese individuals. Yet, there is a paucity of data on the outcomes of PCNL in morbidly obese patients (body mass index [BMI] >40). Methods: Perioperative and stone-related outcomes following PCNL in morbidly obese patients was assessed using a prospective database administered by the Clinical Research Office of the Endourological Society (CROES). A multidimensional match of 97 morbidly obese patients with those of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 25 publications
0
13
0
2
Order By: Relevance
“…A case-control analysis that matched 97 morbidly obese patients (BMI > 40 kg/m 2 ) with 97 normal-weight patients demonstrating a significant impact of BMI on PCNL outcomes [50]. This study showed that SFR decreased with an increase in BMI and this was associated with a higher risk of re-intervention.…”
Section: Interventional Managementmentioning
confidence: 67%
“…A case-control analysis that matched 97 morbidly obese patients (BMI > 40 kg/m 2 ) with 97 normal-weight patients demonstrating a significant impact of BMI on PCNL outcomes [50]. This study showed that SFR decreased with an increase in BMI and this was associated with a higher risk of re-intervention.…”
Section: Interventional Managementmentioning
confidence: 67%
“…A number of mainly retrospective studies have evaluated PCNL outcomes in obese and morbidly obese patients, although to our knowledge there are no reports on outcomes in the super obese [9][10][11][12][24][25][26][27]. Interestingly, the definition of morbid obesity varies, with some studies using BMI ≥ 35 kg/m 2 as the threshold and others using BMI ≥ 40 kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, less uniformity in the reported outcomes of complications, stone-free rates, operating times and need for auxiliary procedures. Results from the PCNL Global Study [10] and from Faerber and Goh [28] suggested a higher complication rate (22.1 vs 6.5%), lower stone-free rate (65.6 vs~79%), longer operating time (112 vs~80 min) and more frequent need for auxiliary procedures (28.1 vs 12.4%) in the morbidly obese vs normal weight patients [10,28]. This contrasts with a number of other retrospective studies, which found no significant association in these variables with BMI [9,11,12,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…11 Several studies have documented the feasibility, safety, and efficacy of PCNL in obese patients. [12][13][14] However, limitations such as small sample size, 15 lack of comparator groups, 16,17 or few patients at BMI extremes 18 have led some experts to assert that alternative treatment modalities, namely flexible ureteroscopy, be considered first-line therapy. 19 Herein, we present our experience and outcomes following PCNL in patients across a wide range of BMI from a large, single-institutional contemporary dataset.…”
Section: Introductionmentioning
confidence: 99%